The Devil's code - Sandford, John (Berkley Books, 2000)
Two seemingly unrelated murders lead ethical thief, artist, and hacker Kidd and his partner LuEllen to uncover a vast electronic conspiracy involving a corporation and a number of U.S. government bureaucrats.